Identification of a novel HLA‐A*11 allele, HLA‐A*11:399, in a Chinese Individual. (12th July 2021) - Wang, Fei; Zhou, Dan; Quan, Zhan‐rou
Abstract : One nucleotide substitution in codon 90 of HLA‐A*11:01:01:01 results in a novel allele, HLA‐A*11:399 .